2011
DOI: 10.1128/jcm.00213-11
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus Species and Other Molds in Respiratory Samples from Patients with Cystic Fibrosis: a Laboratory-Based Study with Focus on Aspergillus fumigatus Azole Resistance

Abstract: Respiratory tract colonization by molds in patients with cystic fibrosis (CF) were analyzed, with particular focus on the frequency, genotype, and underlying mechanism of azole resistance among Aspergillus fumigatus isolates. Clinical and demographic data were also analyzed. A total of 3,336 respiratory samples from 287 CF patients were collected during two 6-month periods in 2007 and 2009. Azole resistance was detected using an itraconazole screening agar (4 mg/liter) and the EUCAST method. cyp51A gene sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
146
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(166 citation statements)
references
References 51 publications
(66 reference statements)
13
146
1
2
Order By: Relevance
“…The Aspergillus cyp51A gene encodes cytochrome P450 sterol 14a-demethylase and is the target for azole drugs. Between 5% and 20% of CF patients exposed to recent itraconazole courses were found to be either colonised or infected with azole-resistant A. fumigatus in recent studies, while, in another study, 4% of A. fumigatus respiratory isolates from a variety of different patient groups (including CF, chronic obstructive pulmonary disease, intensive care unit cases and ABPA) were itraconazole-resistant [104,105,108]. In some instances, azole cross-resistance has also been documented.…”
Section: Antifungal Therapy In Abpa and Safsmentioning
confidence: 97%
See 1 more Smart Citation
“…The Aspergillus cyp51A gene encodes cytochrome P450 sterol 14a-demethylase and is the target for azole drugs. Between 5% and 20% of CF patients exposed to recent itraconazole courses were found to be either colonised or infected with azole-resistant A. fumigatus in recent studies, while, in another study, 4% of A. fumigatus respiratory isolates from a variety of different patient groups (including CF, chronic obstructive pulmonary disease, intensive care unit cases and ABPA) were itraconazole-resistant [104,105,108]. In some instances, azole cross-resistance has also been documented.…”
Section: Antifungal Therapy In Abpa and Safsmentioning
confidence: 97%
“…It has not yet been clearly demonstrated that the beneficial effects of azoles in ABPA and SAFS are due to their antifungal activity as opposed to alterations in concomitantly administered glucocorticosteroid metabolism or independent anti-inflammatory azole effects [43,51]. Most troubling, however, is the emerging evidence that increased azole usage for various medical conditions and (at least in some geographical regions) agricultural applications is leading to a higher prevalence of azole resistance in clinical A. fumigatus isolates, most commonly due to point mutations in the cyp51A gene [100][101][102][103][104][105][106][107][108]. The Aspergillus cyp51A gene encodes cytochrome P450 sterol 14a-demethylase and is the target for azole drugs.…”
Section: Antifungal Therapy In Abpa and Safsmentioning
confidence: 99%
“…1-3 Aspergillus fumigatus (Af) is the most commonly isolated fungus in CF with a prevalence of up to 60%. 4 The fungus is associated with a range of manifestations in CF, most commonly allergic bronchopulmonary aspergillosis (ABPA) and less commonly, aspergillomas and invasive pulmonary aspergillosis. [5][6][7] ABPA affects between 2%-15% of patients with CF (PWCF) and recurrent episodes impact pulmonary function.…”
Section: Abbreviationsmentioning
confidence: 99%
“…In this study, 47 of 921 patients (5.1%) were diagnosed with TR34-L98H and 13 (1.4%) with the TR46-Y121F-T289A mutations. Other mutations have also been described (13)(14)(15)(16). Infections with azole-resistant strains are associated with a very high mortality rate (17).…”
mentioning
confidence: 99%